Demographic and genetic structure of a severely fragmented population of the endangered hog deer (Axis porcinus) in the Indo-Burma biodiversity hotspot - Angom, Sangeeta (PLoS One, 2020)
The population of the globally endangered hog deer (Axis porcinus) has declined severely across its geographic range. Intensive monitoring of its demographic and genetic status is necessary. We examined the demographic and genetic structure of a small hog deer population in Keibul Lamjao National Park (KLNP), located on the western fringe of the Indo-Burma biodiversity hotspot for conservation planning. The distribution pattern of hog deer in the Park was derived based on the presence/absence of faecal pellets in 1 km × 1 km grids. We used double-observer distance sampling method to derive the hog deer abundance and population structure and compared with previous data to derive the population trend. We determined the genetic diversity of the population through microsatellite screening and bottleneck detection. The overall pellet density was 0.34 ± 0.02 pellets km(-2) restricted to only 22.34 ± 0.20 km(2) area of the park. The estimated density of the deer in the park was 1.82–4.32 individuals km(-2). The population showed a declining trend from 2006–08 (p < 0.05, R(2) = 0.916) with 8% annum(-)(1) and an increasing trend from 2003–2018 (p < 0.05, R(2) = 0.9304) with 10% annum(-)(1). The adult male-to-female ratio and fawn-to-doe ratio were 36.2 ± 1.9 males per 100 females and 16.5 ± 0.4 fawns per 100 females, respectively. The molecular examination suggested that the mean number of alleles at 23 loci was 2.70 ± 0.18, the observed heterozygosity (Ho) ranged from 0.26 to 0.63 (mean 0.42 ± 0.02), the expected heterozygosity (He) ranged from 0.23 to 0.73 (χ = 0.51 ± 0.03), and the polymorphic information content (PIC) ranged from 0.2 to 0.67 (χ = 0.43 ± 0.03) indicating a moderate level of genetic diversity. Although no bottleneck in the population was observed, the loss of genetic diversity may affect the evolutionary potential of the species at the site by limiting the selection flexibility. Conservation planning coupled with scientific management regime will help in the long term persistence of the population in the region.